Black Cumin Seed Oilas Hepatoprotector in Decreasing SGPT and SGOT Activity and Increasing p53 Gene Expression in Sprague Dawley Rats Induced by Alloxan - Akrom Akrom; Endang Darmawan; Liesma Yuhelvia (Intelektual Pustaka Media Utama, 2015)
The objective of this research was to determine the effect of BCSO on SGPT/SGOT levels and p53 expression in rats induced by alloxan. This study applied a post test only control group design. A total of 42 SD rats were divided into 6 groups. Group I was normal rats. Group II (negative control) was given alloxan. Group III and IV (treatment groups) were given BCSO with equivalent doses of 6.8 mg/kg and 68 mg/kg thymoquinone, respectively (BCSO 6.8 and BCSO68 groups). Group V (positive control) was given vitamin C. Group VI (control media) were given DMSO. BCSO and Vitamin C are given for 1 week. Alloxan was given on 7th day, i.p. On the 8th day did blood sampling for measurement of SGPT and SGOT levels. Liver retrieval was performed on the 9th day continued immunohistochemistry staining. The average levels of SGPT/SGOT were then analyzed with ANOVA test. p53 expression was analyzed by Kolmogorov Semirnov and Levene then followed by Kruskal Wallis and Mann-Whitney. Statistical tests performed on 95% confidence level. The results showed that the induction of alloxan increased levels of SGPT/SGOT. BCSO68 reduced SGPT /SGOT levels in alloxan-induced rats (p < 0.05). Both BCSO 6.8 and BCSO68 increased the expression of p53 in liver tissue of alloxan – induced rats. Average percentage of p53 expression in group I to group VI were 11.12 ± 0.37; 19.24 ± 4.47; 30.31 ± 1.59; 40.43 ± 1.74; 29.67 ± 0.47; 12.02 ± 1.01, respectively. The result of statistical analysis showed the value of p < 0.05 in all groups except in group III. It can be concluded that BCSO may have hepatoprotective effect and increase the expression of p53 in the liver of alloxan-induced rats.